2019
DOI: 10.3168/jds.2018-15129
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of estrus following an estradiol-progesterone-based ovulation synchronization protocol influences fertility outcomes

Abstract: The objective of this study was to examine the association between increased physical activity at the moment of timed artificial insemination (AI), detected by an automated activity monitor (AAM), and fertility outcomes. This paper also investigated factors affecting estrous expression in general. A total of 1,411 AI events from 1,040 lactating Holstein cows were recorded, averaging 1.3 ± 0.6 (±standard deviation) events per cow. Activity (measured as steps/h) was monitored continuously by a leg-mounted AAM lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 49 publications
4
47
1
4
Order By: Relevance
“…Positive association has been observed in crossbred cows between progesterone concentrations at estrus and d7 post-mating and BCS level. According to the present finding, Madureira et al (2019) reported that lower concentrations of progesterone d 7 post-mating in cows with BCS <2.75 (2.5 ± 0.2 ng/ml) compared to cows with BCS ≥3.0 (3.2 ± 0.1 ng/ml) were found. Positive associations between post-mating and BCS concentrations of progesterone d 7 and the pregnancy rate in cows (Madureira et al, 2019).…”
Section: Effect Of Body Condition Score At Calving On Number Of Servisupporting
confidence: 62%
See 1 more Smart Citation
“…Positive association has been observed in crossbred cows between progesterone concentrations at estrus and d7 post-mating and BCS level. According to the present finding, Madureira et al (2019) reported that lower concentrations of progesterone d 7 post-mating in cows with BCS <2.75 (2.5 ± 0.2 ng/ml) compared to cows with BCS ≥3.0 (3.2 ± 0.1 ng/ml) were found. Positive associations between post-mating and BCS concentrations of progesterone d 7 and the pregnancy rate in cows (Madureira et al, 2019).…”
Section: Effect Of Body Condition Score At Calving On Number Of Servisupporting
confidence: 62%
“…According to the present finding, Madureira et al (2019) reported that lower concentrations of progesterone d 7 post-mating in cows with BCS <2.75 (2.5 ± 0.2 ng/ml) compared to cows with BCS ≥3.0 (3.2 ± 0.1 ng/ml) were found. Positive associations between post-mating and BCS concentrations of progesterone d 7 and the pregnancy rate in cows (Madureira et al, 2019). Spencer and Bazer (2002) stated that post-service progesterone concentrations were positively associated with cows conception rates maybe progesterone is vital for pregnancy maintenance.…”
Section: Effect Of Body Condition Score At Calving On Number Of Servisupporting
confidence: 62%
“…Furthermore, Pereira et al [ 41 ] reported that the reduction in pregnancy loss in cows that expressed oestrus at AI occurred regardless of the diameter of the pre-ovulatory follicle and the hormonal protocol. Madureira et al [ 15 ] elucidated that the actual factor related to increased CR and decreased PL could be the intensity of oestrus expression, irrespective of the reproductive strategy implemented. In the present work, the type of AI with less PL pregnancies included those pregnancies after natural breeding, which may be the deffinitive factor, supporting the results of Madureira et al [ 15 ] because animals inducing bulls to mount and tolerating natural breeding express estrous adequately.…”
Section: Discussionmentioning
confidence: 99%
“…Madureira et al [ 15 ] elucidated that the actual factor related to increased CR and decreased PL could be the intensity of oestrus expression, irrespective of the reproductive strategy implemented. In the present work, the type of AI with less PL pregnancies included those pregnancies after natural breeding, which may be the deffinitive factor, supporting the results of Madureira et al [ 15 ] because animals inducing bulls to mount and tolerating natural breeding express estrous adequately. Moreover, the factor reproductive strategy which included all hormonal protocols and AI after observed oestrus, was not significantly associated with PL in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation